Composition Modification of Iron Oxide Particles Using Activated Carbon for Adsorbtion of Cooper-Polluted Water From Siak River Water Pekanbaru, Riau. (October 2020) - Mardhatillah, Wirdati; Amiruddin, Erwin; Taer, Erman
Abstract: Modification of magnetite (Fe3 O4 ) nanoparticles with activated carbon of Pulai leaveshas been carried out. Magnetite (Fe3 O4 ) nanoparticles were synthesized from natural sand of Padang beach West Sumatra and activated carbon was extracted from Pulai leaves. Structural and morphological properties of magnetite nanoparticles were studied using X-Ray Diffractometer (XRD) and Scanning Electron Microscope (SEM) respectively. Elemental composition of the samples was identified using X-Ray Fluorescence Spectroscopy (XRF). The heavy metal (cooper) adsorption was determined using Ultra Violet Visible light Spectroscopy (UV-Vis). The ability of magnetite(Fe3 O4 ) nanoparticles modified with activated carbon for adsorbing the cooper ion in Siak river water is discussed.The results indicate that magnetite (Fe3 O4 ) nanoparticlesmodified with activated carbon of Pulai leavescan absorb heavy metal Cu contained in Siak river water.